On the (potential) value of coaching - Rynne, S. B.; Crudgington, B.; Dickinson, R. K.; Mallett, C. J. (Routledge handbook of talent identification and development in sport, 2017)
There is moderate empirical evidence that supportive families, coaches, and teachers contribute to athlete development (Rees, Hardy, Giillich, et al., 2016). Of these various social actors, athletes and coaches are considered the two key performers in the sporting context (Mallett & Rynne, 2015). Typically, coaches are adults (and in many cases parents) who by age, position, and perceived knowledge assume a position of leadership, and therefore an inherent power differential exists between coach and athlete (Cassidy, Jones, & Potrac, 2015; Coatsworth & Conroy, 2006). Hence, it is logical to assume that in most cases coaches are influential in sport regardless of the setting (e.g., children, emerging, performance, high performance). This position has received support in the talent literature. For example, Gulbin, Oldenziel, Weissensteiner, and Gagne (2010) found that two-thirds of Australian athletes reported that their coaches were critical and highly influential in their development throughout the athlete pathway. Moreover, athletes reported that coaches increasingly became more important to their development as they progressed to higher competitive levels. They concluded that it was essential to match talented athletes with talented coaches to optimise athlete development. More generally, several researchers in talent development of athletes have argued that expert coaches are foundational to talent identification and development programs (Bullock et al., 2009; Vaeyens, Giillich, Warr, & Philippaerts, 2009). In this chapter, we consider the potential influence of coaches across various forms of athlete involvement. More specifically we: • Explicitly deal with why `value` cannot be assumed with respect to coaching • Position coaches as architects of the sporting environment and consider the work that coaches undertake • Consider the knowledge that underpins this work • Characterise areas of potential impact that coaches can have • Consider coaching in contexts (different parts of models)